Associations of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio with diabetes and prediabetes among adults with hypertension: a cross-sectional study - Meng, Qing; Fan, Shengqiang; Zhang, Li; Shen, Bin; Zou, Chaoping; Sun, Dezhou; Liu, Xianghui; Zhang, Jian; Xu, Shugang (Frontiers in Endocrinology, 2025)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is an emerging composite lipid marker. Prediabetes, characterized by an asymptomatic state with moderate hyperglycemia, is more prevalent than diabetes. This study aimed to elucidate the potential correlation between NHHR and the risk of diabetes and prediabetes among adults with hypertension.MethodsIn this cross-sectional survey, we screened National Health and Nutrition Examination Survey (NHANES)-collected data during 2009-2018, identifying a qualifying population of 10,250 individuals. Weighted multivariate logistic regression and curve fitting evaluated the correlation between the NHHR and the incidence of diabetes and prediabetes. To test differences between subgroups, stratified analyses were performed. Additionally, prediction accuracy of the NHHR was assessed using receiver operating characteristic (ROC) curves.ResultsWe included 10,250 patients with hypertension (mean age, 56.31 ± 16.06 years) including 2,198 with diabetes and 4,138 with prediabetes—a combined prevalence of 61.81%. The fully adjusted model indicated each unit increase in NHHR was associated with a 21% higher risk of diabetes/prediabetes (OR 1.21; 95% CI, 1.15-1.25). Adjustment using multivariable classification models revealed that compared to the lowest NHHR quartile, the odds increased by 41% (OR 1.37; 95% CI, 1.27-1.59, p<0.001) in Q3 and (OR 1.82; 95% CI, 1.62-1.98, p<0.001) in Q4. In patients with hypertension, the NHHR was positively correlated with the prevalence of diabetes and prediabetes, with a nonlinear trend in the fitted curve (nonlinearity, P=0.007). The threshold effect analysis showed that the inflection point for NHHR and the risk of diabetes and prediabetes was 7.09. In particular, when NHHR was below 7.09, a positive correlation was found between NHHR and the risk of diabetes and prediabetes in this population (OR 1.34; 95% CI, 1.28–1.39). Subgroup analyses showed consistent associations across most groups, with a significant interaction in sex.ConclusionsNHHR is positively and non-linearly correlated with diabetes/prediabetes in patients with hypertension, particularly among women. It may serve as a valuable tool for early risk assessment and management.